GAMBARAN PENGETAHUAN ORANG TUA TENTANG PENDIDIKAN SEKS PADA ANAK USIA 0-6 TAHUN DI KECAMATAN SINGKEP BARAT KABUPATEN LINGGA PROVINSI KEPULAUAN RIAU - Megawati '; Ria Novianti; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to describe the parent’s knowledge about child’s sex education in age 0-6 years in Kampung Nelayan Marok Tua Village of Singkep Barat districts of Lingga Regency of Riau Islands province. The benefits are this study will be useful as scientific knowledge and to increase parent’s knowledge about child’s sex education in age 0-6 years. Population and sample in this study were 75 parent’s whose lived in Kampung Nelayan Marok Tua village of Singkep Barat districts of Lingga regency of Riau Islands province. The data collection technique that used in this research is a form with multiple choices questions’s. And the data analysis technique by using a percentage formula. The result showed an overview of parent’s knowledge about child’s sex education, there are 6 aspects; in the aspects of the notion of sex education for early childhood were in the middle category with percentage 62.93%, in the aspects of the principles and objectives about sex education for early childhood were in the middle category with percentage 50.4%. In the aspects of sex education approach for early childhood were in the middle category with percentage 53.33%. The analysis aspect of sex education for early childhood were in the middle category with percentage 58.66%. In the aspects by method of sex education for early childhood were in the middle category with percentage 50.66%. And in the aspects of sex education activities for early childhood were in the high category with percentage 73.33%. Conclusion : with the provision of knowledge about sex education for early childhood right and proper, then the issues of sexual abuse of children who come from parents due to lack of knowledge and lack of proper explanation parents to their children about issues any thing concerning sex education for early childhood will be easier to deal with, because before school and teacher parent who is the primary educator and foremost for children, from families that all education begins included sex education, especially for young children.